2020
DOI: 10.3390/en13174559
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Coal Structure Combinations and Their Influence on Hydraulic Fracturing: A Case Study from the Qinshui Basin, China

Abstract: Coal structure directly correlates to permeability and hydraulic fracturing effects. Underground coal mining indicates that a single coal section generally contains multiple coal structures in superposition, making how to recognise the coal structure combination and predict its influence on coal permeability a challenging problem. Based on well-drilling sampled cores, the geological strength index (GSI), and well-logging data, the DEN, GR, CALX, and CALY were selected to establish a model to predict GSI by mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…To some extent, the petrophysical quantity plates can provide insight into the statistical distribution law related to the coal seam. By referring to information from the neighboring areas [29], it was determined that the…”
Section: Logging the Multi-parameter Interpretation Modelmentioning
confidence: 99%
“…To some extent, the petrophysical quantity plates can provide insight into the statistical distribution law related to the coal seam. By referring to information from the neighboring areas [29], it was determined that the…”
Section: Logging the Multi-parameter Interpretation Modelmentioning
confidence: 99%
“…3 coal seam. Previous studies have shown that its burial depth is 500-1300 m, the coal thickness is 4-10 m, and the gas content is 8-28 m 3 /t [30,31]. Based on the above, basic parameters of the basic model are described as follows: the depth of the coal seam is 1000 m, the thickness of the coal seam is 6 m, and the gas content is 24 m 3 /t.…”
Section: Model Establishmentmentioning
confidence: 99%
“…The Qinshui Basin is located in the southeast of the Shanxi Province, covering an area of about 26,000 km 2 (Figure ). It is rich in coal and coalbed methane resources, and it is the only large basin in China to develop coalbed methane on an industrial scale. Structurally, it is located in the central part of the North China Craton and is generally a large-scale complex syncline with axial NNE–SSW. , After a series of tectonic influence, especially during the Yanshanian and the Himalayan period, the Qinshui basin formed a complex structural setting. …”
Section: Geological Settingmentioning
confidence: 99%
“…32−34 Structurally, it is located in the central part of the North China Craton and is generally a large-scale complex syncline with axial NNE−SSW. 35,36 After a series of tectonic influence, especially during the Yanshanian and the Himalayan period, the Qinshui basin formed a complex structural setting. 37−41 After a series of tectonics and discontinuous deposition, the Qinshui Basin became a residual structural basin with a thickness of 200−3000 m of coal-bearing strata, 26 and under the influence of intermittent uplift and subsidence, multiple periods of transgression occurred in the early and late Carboniferous and early Permian, resulting in obvious regional cycles of coal seams, carbonate rocks, mudstones, and sandstone in the sedimentary strata from the Taiyuan Formation to the Shanxi Formation 43−47 (Figure 1).…”
Section: Geological Settingmentioning
confidence: 99%